Angiotensin II Infusion Does Not Cause Abdominal Aortic Aneurysms in Apolipoprotein E-Deficient Rats - Phillips, Evan H. (J Vasc Res, 2017)
The apolipoprotein E-deficient mouse model has advanced our understanding of cardiovascular disease mechanisms and experimental therapeutics. This spontaneous model recapitulates aspects of human atherosclerosis and allows for the development of dissecting abdominal aortic aneurysms when combined with angiotensin II. We characterized apolipoprotein E-deficient rats and hypothesized that, similar to mice, they would develop dissecting abdominal aortic aneurysms. We created rats with a 16-basepair deletion of the apolipoprotein E gene using transcription activator-like effector nucleases. We imaged the suprarenal aorta for 28 days after implantation of miniosmotic pumps that infuse angiotensin II (200 ng/kg/min). Blood pressure, serum lipids and lipoproteins, and histology were also analyzed. These rats did not develop pathological aortic dissection, but we did observe a decrease in circumferential cyclic strain, a rise in blood pressure, and microstructural changes in the aortic medial layer. We also measured increased serum lipids with and without high fat diet administration but did not detect atherosclerotic plaques. Chronic infusion of angiotensin II did not lead to formation of dissecting abdominal aortic aneurysms or atherosclerosis in the rats used in this study. While reduced amounts of atherosclerosis may explain this resistance to dissecting aneurysms, further investigation is needed to fully characterize species-specific differences.